Urbanisation and its impact on sustainable development in Harare: a case of Harare south - Mangwende, Priscillar (Midlands State University, 2017)
Urbanisation in Zimbabwe is associated with sustainable development challenges especially in the major cities such as Gweru, Kwekwe, Mutare, Masvingo and most importantly Harare. This is evidenced by the fact that Zimbabwe is also one of the countries which failed to meet the Sustainable Development Goals by the year 2015. The research therefore focuses on how urbanisation has impacted on the sustainable development of Harare which is the most affluent city in the country. Through participatory observations, interviews and secondary sources the study revealed that urbanisation had indeed threatened the sustainability of the city. Urbanisation has compromised the provision of basic social services such as education, health, adequate housing, water and sanitation, transport and communication systems, employment and the fair distribution of resources among others. This research also examined Harare’s population growth and dynamics and urbanisation control measures in the face of increasing urbanisation as well as possible solutions to curb the phenomenon are also discussed.